Yannis Stouraitis (ed.) Identities and Ideologies in the Medieval East Roman World. - Sandiford, Alex (Journal of Greek Archaeology, 2025)
Identity and ideology are currently attracting a fast-growing enthusiasm in academic research and debate, and Byzantine studies are benefitting especially strongly from this trend. That is why Yannis Stouraitis’ new edited book will be a welcome and advantageous addition to the Byzantinist’s library. With great diligence and creativity, Stouraitis brings together seventeen scholars to expose the multifaceted and conflicting constructions of ideology and identity in Byzantium and her peripheries.